Experimental and Numerical Study on the Low Cycle Fatigue Behaviour of a Cast Hybrid Metal Matrix Composites - Iqbal, AKM Asif; Arai, Yoshio (2014)
The low-cycle fatigue (LCF) behavior specially the fracture initiation mechanism in a cast hybrid metal matrix composite (MMC) has been studied experimentally and numerically. Conventional three point bending fatigue test has been carried out and factographic analysis has been conducted to observe the fracture initiation site. Experimental results showed that microcracks in LCF initiated at the particle—matrix interface which was located in the hybrid clustering region. Due to continued fatigue cycling, the interface debonding occurred, created additional secondary microcracks and the microcrack coalesced with other nearby microcracks. As far as the numerical study is concerned, three dimensional (3-D) unit cell models of hybrid MIMC consists of reinforcement clustering and non-clustering regions were developed by using finite element method (FEM). The stress-strain distribution in both the reinforcement clustering and non-clustering regions were analyzed. The numerical results confirmed that the stress concentration occurred on the reinforcement—matrix interfaces located in the clustering region and provide reasonable agreement with the experimental observations.